2022
DOI: 10.3389/fimmu.2022.848248
|View full text |Cite
|
Sign up to set email alerts
|

Normal Light-Dark and Short-Light Cycles Regulate Intestinal Inflammation, Circulating Short-chain Fatty Acids and Gut Microbiota in Period2 Gene Knockout Mice

Abstract: Regular environmental light–dark (LD) cycle-regulated period circadian clock 2 (Per2) gene expression is essential for circadian oscillation, nutrient metabolism, and intestinal microbiota balance. Herein, we combined environmental LD cycles with Per2 gene knockout to investigate how LD cycles mediate Per2 expression to regulate colonic and cecal inflammatory and barrier functions, microbiome, and short-chain fatty acids (SCFAs) in the circulation. Mice were divided into knockout (KO) and wild type (CON) under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 72 publications
0
15
0
Order By: Relevance
“…42 Meanwhile, our results for biomarkers with LDA > 4 of the bacterial flora showed that the dominant communities in the H-GOS group were Rikenella and Parabacteroides , compared with the AGE group. Rikenella was classified as a butyrate-producing bacterium, while Parabacteroides ASF519 and Parabacteroides johnsonii have been reported to produce propionate by succinate-conversion, 43–45 which was consistent with high-dose GOS supplementation leading to a significant increase in butyrate and propionate levels in AGE-induced mice. Accumulating evidence suggested that the cells lining the mucosa were affected by SCFAs in the intestinal lumen.…”
Section: Resultsmentioning
confidence: 66%
“…42 Meanwhile, our results for biomarkers with LDA > 4 of the bacterial flora showed that the dominant communities in the H-GOS group were Rikenella and Parabacteroides , compared with the AGE group. Rikenella was classified as a butyrate-producing bacterium, while Parabacteroides ASF519 and Parabacteroides johnsonii have been reported to produce propionate by succinate-conversion, 43–45 which was consistent with high-dose GOS supplementation leading to a significant increase in butyrate and propionate levels in AGE-induced mice. Accumulating evidence suggested that the cells lining the mucosa were affected by SCFAs in the intestinal lumen.…”
Section: Resultsmentioning
confidence: 66%
“…It was suggested that Dubosiella may contribute to alleviation of insulin resistance and lipid metabolism. Interestingly, it was reported that the Erysipelatoclostridium is one of the dominant intestinal genera in obesity mice ( 61 ), which was considered to be harmful to human health ( 62 ). However, the relative abundance of Erysipelatoclostridium in this study was significantly positively associated with propionic acid, n -valeric acid, acetic acid, isovaleric acid, n -butyric acid, isobutyric acid and significantly negatively related to FFA level.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that ACADL , ALDH2 , FGFRL1 , SIX1 and PLCB1 are involved in fatty acid degradation, fatty acid metabolism and the PPAR signaling pathway ( Bedford et al, 2020 ; Fang et al, 2021 ; Shi et al, 2021 ). In addition, NHE1 and PCCA participate in butyric acid metabolism, phenylalanine metabolism and fatty acid metabolism ( Fu et al, 2022 ; Zhen et al, 2022 ). Our research found that acetate was used to form IMF lipid by the PPAR signaling pathway.…”
Section: Discussionmentioning
confidence: 99%